BUSINESS ANALYSIS OF FRESWATER FISH ENLARGEMENT IN POND OF BAGAN BESAR VILLAGE BUKIT KAPUR DISTRICT CITY DUMAI RIAU PROVINCE - Dukut Tri Sadono; Hamdi Hamid; Eni Yulinda (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted in June 2013 in Bagan Besar village’s Bukit Kapur District’s Dumai Riau Province. The analysis method was conducted by survey. Where farmers Catfish 3 people, African catfish 3 people and farmers tilapia 3 people, 9 freshwater fish farmers have been selected at random. Respondens was choosen by cluster sampling method that consist of three catfish farmer, theree african catfish and three tilapia farmer. Totaly, 9 freshwater fish farmers was selected randomly.This research aimed to determine how much the total cost of production, revenue and operating income in the freshwater fish rearing ponds at Bagan Besar village Bukit Kapur District City Dumai Riau Province. The financial analys result showed that business was profitable, so that business of freshwater fish enlargement’s in bagan besar worthy to continue and develop. Net provit value criteria catfish was Rp. 937.761,-/harvest. Catfish Rp. 1.581.575,-/harvest and Tilapia Rp. 1.501.101,-/harvest.Keywords: business analysis, ponds, Catfish, African catfish, Tilapia